Nurse Information Security Policy Compliance, Information Competence, and Information Security Attitudes Predict Information Security Behavior. - Kang, Purum; Kang, Jiwon; Monsen, Karen A. (CIN: Computers, Informatics, Nursing, 2023)
Nurses' attitudes toward information security can influence the hospital's information resources management and development. This study investigated the relationships between nurses' information security policy compliance, information competence, and information security attitudes, which are factors that influence information security behavior. Data were collected during September 2020. The participants were 200 clinical nurses from a general hospital in Korea. The self-reported questionnaire included questions on nurses' general characteristics, information security policy compliance, information competence, and information security attitudes. Information security policy compliance (r = 0.554, P < .001) and information competence (r = 0.614, P < .001) were positively associated with information security attitudes. Predictors of nurses' information security attitudes were information competence (0 = .439), information security policy compliance (0 = .343), prior information security-related education (0 = .113), and job position (nurse manager; 0 = .101). Implications for practice include the need for strategies to develop information security policy compliance and information competence to improve information security behavior, includingdifferent approaches tailored to nurses' job positions and previous information security education. This research was supported by the Basic Science Research Program through the National Research Foundation of Korea (NRF), funded by the Ministry of Education (NRF-2020R1I1A1A01068239), and the Center for Women in Science, Engineering and Technology Grant, funded by the MIST under the Program for Returners into R&D (WISET-2020-561).